Philippa M. Steele, Exploring writing systems and practices in the Late Bronze Age Aegean. - Dickinson , Oliver (Journal of Greek Archaeology, 2024)
This book represents the work conducted by the author as principal investigator of the project Contexts of and Relations between Early Writing Systems (CREWS), funded by the European Research Council, and is the culmination of a series of CREWS open access volumes published with Oxbow Books. As the title and Introduction make clear, it is concerned with the Aegean Bronze Age scripts, and particularly with the interrelated problems of the relationship between Linear A and Linear B, and the failure of Linear B to survive the downfall of the palatial societies, whereas a script developed in Cyprus from Linear A during the Late Bronze Age survived in use into at least Late Classical times.